Rural women workers in nineteenth-century England : gender, work and wages - Verdon, Nicola, 1970- (Boydell Press, 2002)
The work performed by women who lived in the nineteenth-century English countryside is still an under-researched issue. Verdon directly addresses this issue, placing the rural female labourer centre stage for the first time. The involvement of women in the rural labour market as farm servants, as day labourers in agriculture, and as domestic workers, are all examined using a wide range of printed and unpublished sources.